Cortical cholinergic dysfunction correlates with microglial activation in the substantia innominata in REM sleep behavior disorder. (December 2020) - Stær, Kristian; Iranzo, Alex; Stokholm, Morten G.; Østergaard, Karen; Serradell, Mónica; Otto, Marit; Svendsen, Kristina B.; Garrido, Alicia; Vilas, Dolores; Santamaria, Joan; Møller, Arne; Gaig, Carles; et al.
Abstract: Introduction: In vivo PET studies in patients with isolated REM sleep behavior disorder (iRBD) have shown presence of neuroinflammation (microglial activation) in the substantia nigra, and reduced cortical acetylcholinesterase activity, suggestive of cholinergic dysfunction, that was more widespread in patients with poorer cognitive performances. This study aimed to explore whether reduced cortical acetylcholinesterase activity in iRBD is linked to microglial activation in the substantia innominata (SI), the major source of cholinergic input to the cortex. Methods: We used 11 C(R)-PK11195 and 11 C-Donepezil PET to assess levels of activated microglia and cholinergic function, respectively, in 19 iRBD patients. 11 C(R)-PK11195 binding potential (BPND ) and 11 C-Donepezil distribution volume ratio (DVR) values were correlated using the Pearson statistic. Results: We found that a lower cortical 11 C-Donepezil DVR correlated with a higher 11 C(R)-PK11195 BPND in the SI ( r  = −0.48, p  = 0.04). At a voxel level, the strongest negative correlations were found in the frontal and temporal lobes. Conclusion: Our results suggest that reduced cortical acetylcholinesterase activity observed in our iRBD patients could be linked to the occurrence of neuroinflammation in the SI. Early modulation of microglial activation might therefore preserve cortical cholinergic functions in these patients. Highlights: Cortical cholinergic function in iRBD may be linked to basal forebrain inflammation. Basal forebrain projections to frontal and temporal lobes were the most affected. Some iRBD patients have abnormally increased basal forebrain microglial activation.